PENDEKATAN GREEN SUPPLY CHAIN MANAGEMENT UNTUK PENGUKURAN KINERJA RANTAI PASOK HIJAU PADA PERUSAHAAN PRODUKSI ALAT RUMAH TANGGA PLASTIK - Sunantha, May Calysta; Kosasih, Wilson; Andres, Andres (Jurnal Mitra Teknik Industri, 2025)
This study focuses on evaluating green supply chain performance within a plastic-based household product manufacturer, specifically in the production of drinking glasses. Data collection involved questionnaires and interviews with company representatives. Findings from the interviews revealed a primary challenge in accurately forecasting sales demand, creating uncertainties in production and storage and often leading to overstock or stockouts, both of which negatively affect customer satisfaction. Over the last six months, significant discrepancies between forecasted and actual demand were recorded, with differences of 92, 90, 84, 37, 74, and 80 cartons respectively. To address these issues, the research applies a Green Supply Chain Management (GSCM) approach using the Green Supply Chain Operations Reference (GSCOR) model, alongside Key Performance Indicators (KPI), the Analytical Hierarchy Process (AHP), the Objective Matrix (OMAX), and the Traffic Light System (TLS). KPIs are measured across five core processes: plan, source, make, deliver, and return. This study aims to improve forecast accuracy, support the implementation of more effective and efficient strategies, and assess the extent of the company's environmental sustainability practices, ultimately contributing to better environmental practices within the organization.